Russia's military capabilities: "Great Power" ambitions and reality - Margarete Klein (Stiftung Wissenschaft und Politik (SWP), 2009)
Russia's political and military leaders, increasingly after Putin's second term in office, have conveyed the notion of the country being (again) a Great Power. To buttress such claims, they have asserted that Russia had made progress not only in economic affairs but also experienced a significant military revival. Military parades and large-scale maneuvers are being held again and rearmament programs put in place.The country's strategic nuclear arsenal, however, remains the main pillar of the Great Power status. The conventional forces lack the capabilities for global power projection and effectiveness leaves much to be desired. This is due to obsolete equipment, inadequate training and outdated operational concepts. Military reforms announced in October 2008 are to overcome such deficits. Russia's armed forces with their reliance on conscription and mass mobilization are to be transformed to smaller, more modern, better trained, better equipped and more flexible combat-forces.Success of the reforms would not fundamentally alter the balance of forces with Nato but enable Moscow to strengthen its preponderance on post-Soviet space. For that very reason Europe should be reviving conventional arms control. On the whole, chances for a comprehensive implementation of the reforms are relatively slim because, first, Russia's financial resources and its defense industry are hardly able to cover the enormous requirements for modernization. Second, in view of the country's demographic crisis, it is evident that the problems of recruitment will become more acute. Third, there is as yet no coherent requirement profile for the armed forces. These considerations warrant the conclusion that the gap between Great Power claims and actual capabilities in military affairs will remain
Keywords: 320; Russische Föderation; Heer